Тюркская литература крымчаков - Янбай, Я.С. (Материалы по археологии, истории и этнографии Таврии, 2001)
A brief look at the Krimchaks’ literary works shows that they have common features: A majority of the works was intended for performing aloud. This applies equally both to the Krimchak songs and to the biblical translations. The oral character of songs, verses and tales is beyond any doubt. The religious literature represented on books and manuscripts consists, for instance, of the Krimchak translations of the Book of Ruth, the Book of Song of Songs, a prayer book and some copies of the service for Day of the destruction of Jerusalem, etc. All these texts were also performed orally. It is known that the performing by evident articulation all of Jewish religious texts is the custom. But I mean not this, I mean the Krimchaks performed their literary works in audience.